Elisabeth Le Guin. 2006. Boccherini's Body: An Essay in Carnal Musicology. Berkeley and Los Angeles: University of California Press. - Cusick, Suzanne G. (Current Musicology, 2007)
In early 2006, I did something I had never done before. I sent a musicology book as a gift to a friend. No, to two friends, one a former musicologist who now works as a gambist, the other a former musicologist who now works as a writer. I wrote to each of them that Elisabeth Le Guin's Boccherini's Body: An Essay in Carnal Musicology had restored my faith in musicology.